Open IT-Based Innovation: Moving Towards Cooperative IT Transfer and Knowledge Diffusion IFIP TC 8 WG 8.6 International Working Conference, October 22-24, 2008, Madrid, Spain - León, Gonzalo; Bernardos, Ana M.; Casar, José R.; Kautz, Karlheinz; DeGross, Janice I.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2008)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of refereed international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springer.com. For more information about IFIP, please visit www.ifip.org.
Studies on Diffusion and Adoption -- The Diffusion of Research on the Adoption and Diffusion of Information Technology -- Citation Patterns in MIS: An Analysis of Exemplar Articles -- Understanding the Diffusion and Adoption of Telecommunication Innovations: What We Know and What We Don’t Know -- Key Aspects in Innovation -- Explicit as Enabler for Understanding the Tacit -- Applying Usage Models to Innovate Information Technology Solutions -- Seeking the Face of Innovation with the Ethical Compass of Emmanuel Lévinas -- Cross-Organizational and Cultural Issues -- Effects of Cultural Orientation on Attitude Toward Anonymity in E-Collaboration -- Exploring the Influence of Collectiveness on Value Creation Adoption in an Information Technology Organization -- Interorganizational Systems Adoption: A Socio-Technical Perspective -- Analysis of Cases -- Technological Frame Incongruence, Diffusion, and Noncompliance -- Xenia: A Metaphor for Sense-Making and Acting in Information Systems Innovation -- Who Has the Power Over Spaces of Innovation? The Role of Technology in ICT-Triggered Change Processes -- Open Innovation Experiences -- Deciding on Open Innovation: An Exploration of How Firms Create and Capture Value with Open Source Software -- Knowledge Diffusion in ERP Development: The Case of Open Source ERP Downloads -- Toward a User Driven Innovation for Distributed Software Teams -- Design Science and Cases in IT -- Homeward Bound: Ecological Design of Domestic Information Systems -- The Role of Competencies and Interests in Developing Complex Information Technology Artefacts: The Case of a Metering System -- The Vehicle Ecosystem -- Case Studies in Telecommunications -- Examining Factors Influencing the Behavioral Intention to Adopt Broadband in Malaysia -- Standardization as an Arena for Open Innovation -- Crossing the Chasm: From Adoption to Diffusion of a Telehealth Innovation -- Case Studies in Software Businesses -- Evolution of Secondary Software Businesses: Understanding Industry Dynamics -- A Study of the Risks in an Information System Outsourcing Partnership -- Open Innovation and the Erosion of the Traditional Information Systems Project's Boundaries -- Public Administration and Government -- Public Procurement of IS/IT Services: Past Research and Future Challenges -- The Invisible Hand: Governmental Influences on the Field of Play During the Production and Diffusion of Mobile TV -- Opening Public Administration: Exploring Open Innovation Archetypes and Business Model Impacts -- On-Going Research -- Community for Innovations: Developing an Integrated Concept for Open Innovation -- Governance Structures for Open Innovation: A Preliminary Framework -- Reassembling the Information Technology Innovation Process: An Actor Network Theory Method for Managing the Initiation, Production, and Diffusion of Innovations -- Panels -- Open Innovation in Mobile and Convergent Communications -- Corporate Experiences in Open Innovation -- Notes from Industry Experience -- Open, Collaborative Innovation in the 21st Century -- Applying Open Innovation Principles for Triggering and Accelerating Innovations: The Experience of Ericsson Spain, 2004 Through 2007 -- Annex -- Information Technology Diffusion in Academic Teaching: An Institutional Perspective.
Keywords: Computers; Application software; Multimedia information systems; Theory of Computation; Information Systems and Communication Service; Information Systems Applications (incl. Internet).; Multimedia Information Systems